Story of Rubidium-82 and Advantages for Myocardial Perfusion PET Imaging - Chatal, Jean-François; Rouzet, François; Haddad, Ferid; Bourdeau, Cécile; Mathieu, Cédric; Le Guludec, Dominique (Frontiers in Medicine, 2015)
Rubidium-82 has a long story, starting in 1954. After preclinical studies in dogs showing that myocardial uptake of this radionuclide was directly proportional to myocardial blood flow (MBF), clinical studies were performed in the 80s leading to an approval in the USA in 1989. From that time, thousands of patients have been tested and their results have been reported in three meta-analyses. Pooled patient-based sensitivity and specificity were, respectively, 0.91 and 0.90. By comparison with 99mTc-SPECT, 82Rb PET had a much better diagnostic accuracy, especially in obese patients with body mass index ≥30 kg/m2 (85 versus 67% with SPECT) and in women with large breasts. A great advantage of 82Rb PET is its capacity to accurately quantify MBF. Quite importantly, it has been recently shown that coronary flow reserve is associated with adverse cardiovascular events independently of luminal angiographic severity. Moreover, coronary flow reserve is a functional parameter particularly useful in the estimate of microvascular dysfunction, such as in diabetes mellitus. Due to the very short half-life of rubidium-82, the effective dose calculated for a rest/stress test is roughly equivalent to the annual natural exposure and even less when stress-only is performed with a low activity compatible with a good image quality with the last generation 3D PET scanners. There is still some debate on the relative advantages of 82Rb PET with regard to 99mTc-SPECT. For the last 10 years, great technological advances substantially improved performances of SPECT with its accuracy getting closer to this of 82Rb/PET. Currently, the main advantages of PET are its capacity to accurately quantify MBF and to deliver a low radiation exposure.